Bibliometric overview of carbon and particulate matter control and emissions - Lírio, Ulisses; Portella, Andreza (National Journal of City Management, 2021)
This research presents a bibliometric overview of the state of the art around the world regarding carbon emission and control of particulate matter, focusing on keywords, connection networks between author, countries, and quantitative and temporal analysis of publications. The method used was based on the features of the software Vosviewer version 1.6.15, and data extraction for processing of the Scopus database resulting in a sample of 102 papers between the years 2010 and 2020. The results show that research on the topic is still recent and there is no scientific homogeneity in the approaches, they also show that oriental researchers are the ones with more connection networks and although researchers in general are not very connected, the general used keywords have many connections, with emphasis on the term “particle (of particulate matter)” most used in average in 2018. China has 3 lines of research: 1. passive removal through plants like sea lettuce but with little influence; 2. removal using technology such as washing filters and technological Nano; 3. technological with coating made of metallic materials capable of capturing carbon. The western, in general, led by American research, uses passive solutions, by removing pollutants with different types of plants and seeking to find value for the tons of carbon removed by the plants.